Tuning of Quantum Emitters in Hexagonal Boron Nitride - Mendelson, Noah; Nikolay, Niko; Xu, Zai Quan; Tran, Toan Trong; Sadzak, Nikola; Bohm, Florian; Sontheimer, Bernd; Benson, Oliver; Toth, Milos; Aharonovich, Igor (2019 Conference on Lasers and Electro-Optics, CLEO 2019 - Proceedings, 2019)
We demonstrate two different techniques to tune quantum emitters in hBN, achieving record tuning magnitudes for a solid state quantum emitter, as well as dynamic and reversible modulation of the emitters through both methods).
CRIS-Team Scopus Importer:2023-04-20